Impacts of electrode coating irregularities on polymer electrolyte membrane fuel cell lifetime using quasi in-situ infrared thermography and accelerated stress testing. (22nd March 2018) - Phillips, Adam; Ulsh, Michael; Neyerlin, K.C.; Porter, Jason; Bender, Guido
Abstract: In-line quality control diagnostics for roll-to-roll (R2R) manufacturing techniques will play a key role in the future commercialization of the polymer electrolyte membrane fuel cell (PEMFC) used in automotive applications. These diagnostics monitor the fabrication of the membrane electrode assembly (MEA), which detect and flag any non-uniformity that may potentially harm PEMFC performance and/or lifetime. This will require quantitative thresholds and a clear distinction between harmful defects and harmless coating irregularities. Thus, novel fuel cell hardware with quasi in-situ infrared (IR) thermography capabilities is utilized to understand how bare spots in the cathode electrode impact MEA lifetime. An accelerated stress test (AST) simulates chemical and mechanical degradation modes seen in vehicular operation. The actual open circuit voltage and rate of change of this voltage are used as in-situ indicators for MEA failure, enabling capture of the progression of failure point development. Bare spot coating irregularities located at the center of the electrode were found to have no impact on MEA lifetime when compared to a pristine MEA. However, MEA lifetime was found to be considerably shortened when these same irregularities are located at the cathode inlet and, especially, the anode inlet regions of the fuel cell. Highlights: Used quasi in-situ IR thermography and ASTs to study MEA failure point development. Determined that irregularities centered on the electrode didn't impact MEA lifetime. Saw that MEA lifetime was reduced when irregularities located near the gas inlets.